(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Hearing Loss is a common public health issue among middle aged and elderly individuals, with significant effects on communication, social functioning and quality of life.Hearing loss in elderly patients is one of the commonest health issue now a days in Bangladesh. Noise pollution, Ototoxicity, Genetic predisposition, Metabolic disorders, Otological diseases etc. are contributing more or less for this major health issue. In this study we have tried to analyze the clinical presentation, audiological characteristics and etiological profile of hearing loss in patients presenting after the age of 40. Material and methods: This is a prospective cross- sectional study was conducted at Medical Centre Hospital, Chattogram from January 2023 to July 2024. 150 consecutive patients aged >40 years presenting with a chief complaint of hearing loss underwent detailed history-taking, otoscopic examination, and pure-tone audiometry. HRCT of temporal bone and MRI of brain were done in selected cases to establish the diagnosis of Idiopathic hearing loss. Data on presentation, type, degree, and configuration of hearing loss were analyzed. Data were analyzed using SPSS version 26. Descriptive statistics were presented as means ± standard deviation for ‘continuous variables’ and as numbers and percentages for ‘categorical variables’ Results: The mean age of presentation was 62.4 ± 11.8 years. The most common presenting symptom was difficulty in hearing speech in noise (86.7%) followed by tinnitus (68%) and requiring increased television volume (61.3%). The most frequent type of hearing loss was sensorineural (72%) followed by mixed (18.7%) and conductive (9.3%). Bilateral symmetrical hearing loss was present in 78% of cases. Presbycusis was the leading etiological diagnosis (44.7%) followed by noise-induced hearing loss (20.7%) and chronic otitis media (12.7%). A significant portion of patients (59.3%) never sought medical advice prior to testing. Conclusion: Hearing loss in adults over 40 is predominantly sensorineural, bilateral, and characterized by high-frequency loss. Difficulty understanding speech in noisy environments is the most debilitating symptom. There is a significant gap between the perception and reality of hearing impairment, underscoring the need for proactive screening and counseling in this age group. JCMCTA 2025 ; 36 (2) : 31-34